Shedding Light on the Antioxidant Activity of Bee Venom Using a 2,2-Diphenyl-1-Picrylhydrazyl Assay in a Detergent-Based Buffer - Alessandro Orrù; Barbara Pittau; Francesca Pettinau (Molecules)
Honeybee venom (HBV) is a complex mixture of proteins and enzymes used in traditional medicine to treat various ailments. HBV has multiple pharmacological effects, making it a promising therapeutic agent in several medical areas. In addition, HBV has many potential cosmetic applications as an anti-aging agent and for the treatment of various skin conditions. HBV’s antioxidant properties are also of great interest, as oxidative stress contributes to the onset and progression of many diseases. Several attempts have been made to assess HBV’s antioxidant activity, mainly using the DPPH assay. However, variability in experimental protocols and the lack of experimental details make the interpretation of results difficult. In this study, we aim to address the source of this variability by investigating the antioxidant activity of HBV in a detergent-based buffer across a range of pH values (from 3 to 7.5). We also analyze the contribution of melittin, the major component of HBV. Our results demonstrate that the DPPH radical scavenging activity of HBV is strongly influenced by the solvent used and by pH. Specifically, we show, for the first time, that HBV exhibits antioxidant activity under mildly acidic conditions, following a complex fast + slow reaction pattern. Interestingly, melittin contributes only partially to the total antioxidant activity of HBV. Overall, this work provides new insights into the antioxidant properties of HBV.